Laying the Foundations of Continuing Education in Health in the Family Health Strategy - Cleson Moura; Katia Moreira; Andreia Costa; Cristina Lavareda Baixinho; Maria Adriana Henriques; Marcelle Miranda da Silva (MDPI AG, 2022)
Primary healthcare must guarantee health and well-being for the community as a whole, ensuring equity and quality in different responses. For this goal to be achieved, teams must be trained and integrated, and service flows must be functional. Continuing education in health, as a form of training professionals in the workplace, helps to center responses around the needs and preferences of people and families, and to balance the fulfillment of demands by using better work management as a starting point. The objectives of the present qualitative study were to elucidate the meaning given by health professionals who developed their activities in the Family Health Strategy in order to continue education in health, and to discuss the qualification and structuring of work management with this type of education as a background. The methodology used was Straussian grounded theory. Thirty professionals in four Brazilian health units who had experience in the family health field participated in the study. Data were collected between June 2018 and May 2019. Based on three categories, the emerging substantive theory was as follows: laying the foundations of continuing education in health in a collective dialogic and dialectical effort to contribute to the qualification of the work processes in the Family Health Strategy. The professionals' accounts showed that they recognize the importance of continuing education in health and the need to discuss it, given its potential to transform and to assist in the education of professionals with autonomy in the management of their work processes.